Complete Herb Book - McVicar, Jekka (London Kyle Cathie, 1997)
An A-Z guide to herbs which explains how to grow and maintain them, how and when to use them in the kitchen, and what properties they have for medicinal, cosmetic and household purposes. It includes information on each herb's history and folklore, and tips on cooking with them
Include Color Illustration and Index
Keywords: Herbs -- Herb gardening -- Cooking (Herbs)